Sociopragmatic Analysis of Multilingual Background Speech Acts of Indonesian Language and Literature Education Students FKIP Jambi University - Andiopenta, Andiopenta; Pratama, Deri Rachmad; Yusra, Hilman; Saputra, Ade Bayu (Journal of Social Science Utilizing Technology, 2024)
Background. Indonesian Language and Literature Education Students, the Faculty of Teacher Training and Education (FKIP) at Jambi University annually accepts students who are very diverse in culture. However, in general, from year to year, it can be seen that the dominant students are students from Jambi, Kerinci, Javanese, Toba Batak, Minang, Bugis and Palembang Malay backgrounds. Purpose. This research aims to describe the types, functions and politeness of speech acts developed by students of Indonesian Language and Literature education at the Faculty of Teacher Training and Education, Jambi University whose mother tongue is from a multilingual background. Method. This research is qualitative descriptive research. Data was collected from 28 informants. Data was collected using free listening techniques in various settings on campus, as well as recordings and field notes. Data were analyzed using the flow technique from Miles and Huberman through data reduction steps, data presentation, and drawing conclusions. Data validity techniques used triangulation techniques of theory and methods. Results. The research results can be seen from the types of illocutionary speech acts formed in multilingual student speech events, including speech acts; (1) commissive, (2) assertive, (3) declarative, (4) expressive, and (5) directive. Likewise, the function of expressed speech acts is a function; (1) competitive, (2) fun, (3) cooperative, and (4) conflicting.  Meanwhile, the politeness that is adhered to is; (1) Maxim of wisdom, (2) maxim of generosity, (3) maxim of praise, (4) maxim of humility, (5) maxim of agreement, and (6) maxim of sympathy. In terms of interference, speakers who are often interfered with are Minang, Jambi Malay, Palembang and Kerinci speakers, namely phonological interference. Conclusion. In terms of language use, those on campus are dominated by the use of Indonesian, because the average use of Indonesian is above average. However, the highest are speakers of Batak and Bugis languages.